Genetic variation of early height growth traits at the xeric limits of Austrocedrus chilensis (Cupressaceae) - Aparicio, Alejandro (2010)
The study of the genetic variation of early height growth traits in seedlings helps to predict the possible outcomes of tree populations in the face of climate change. Second-year height growth of 10 geographically marginal populations of Patagonian cypress (Austrocedrus chilensis (D. Don) Pic. Ser. et Bizzarri) (Cupressaceae) was characterized under greenhouse conditions. Variation among and within an average of 15 open-pollinated families (comprising 21 seedlings per family) for each population was analysed for six size and timing traits obtained from fitted Boltzmann growth curves.The among-family and among-population variances were 4.03% and 2.74% of the total phenotypic variation, while the residual variance was 84.57% on average. Genetic differentiation among populations was low, except for the maximum growth rate (QST = 0.35) and for growth initiation (QST = 1). For most traits, genetic variation and heritability were variable across populations, except for growth initiation, which showed in general null intra-population levels of genetic variance. Although no direct associations were found between the additive genetic variation and latitude or altitude, the north range of the distribution was more variable for the pool of the analysed traits. Although most extreme-marginal populations of A. chilensis would be very limited in their ability to evolve if climate in north-west Patagonia turns drier and warmer, their long-term persistence could largely rely on a phenotypic diversification strategy.